2009
DOI: 10.1099/jmm.0.013383-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of periodontopathic bacteria in atherosclerotic plaques from coronary arteries

Abstract: Oral pathogens, including periodontopathic bacteria, are thought to be aetiological factors in the development of cardiovascular disease. In this study, the presence of Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum-periodonticum-simiae group, Porphyromonas gingivalis, Prevotella intermedia, Prevotella nigrescens and Tannerella forsythia in atheromatous plaques from coronary arteries was determined by real-time PCR. Forty-four patients displaying cardiovascular disease were submitted to periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
121
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(134 citation statements)
references
References 41 publications
5
121
1
7
Order By: Relevance
“…Oral bacteria can enter the circulation and cause bacteraemia by actively crossing the periodontal epithelium [1820], or by being inoculated through mechanical procedures, including periodontal debridement, flossing and brushing [21,22]. Periodontal pathogens, such as Aggregatibacter actinomycetemcomitans, Treponema denticola and Porphyromonas gingivalis are also capable of invading endothelial cells [2327], and they have been detected in atherosclerotic plaques, heart valves, aortic aneurysms, carotid and coronary vessels [2833]. Studies in a variety of animal models have demonstrated that recurrent bacteraemia or oral administration with P. gingivalis can enhance atherogenesis [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Oral bacteria can enter the circulation and cause bacteraemia by actively crossing the periodontal epithelium [1820], or by being inoculated through mechanical procedures, including periodontal debridement, flossing and brushing [21,22]. Periodontal pathogens, such as Aggregatibacter actinomycetemcomitans, Treponema denticola and Porphyromonas gingivalis are also capable of invading endothelial cells [2327], and they have been detected in atherosclerotic plaques, heart valves, aortic aneurysms, carotid and coronary vessels [2833]. Studies in a variety of animal models have demonstrated that recurrent bacteraemia or oral administration with P. gingivalis can enhance atherogenesis [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a study where bacterial DNA was identified in atherosclerotic plaques, 51.5% of the patients tested positive for Chlamydia in their atheromas (17). Several studies suggest an oral source for atherosclerotic plaque-associated bacteria (18)(19)(20)(21). However, to date, no single study has directly compared the microbial diversity of oral, gut, and atherosclerotic plaque microbiotas within individuals.…”
mentioning
confidence: 99%
“…[13][14][15] Periodontal pathogens were found to be the possible association between periodontal disease and atherosclerosis. [16][17][18][19] Atherosclerosis is a chronic inflammatory disease of artery vessels, starting from the endothelial injury and thrombus formation in the advanced plaque. 20,21 Atherogenesis development may be caused by multiple mechanism which induced by lipopolysaccharides (LPS) from periodontal pathogens in the formation of pro-atherogenic in lipid profile.…”
Section: Introductionmentioning
confidence: 99%